CULTURAL AND ANAMORPHIC CHARACTERIZATION OF TRICHODERMA ISOLATES ISOLATED FROM RHIZOSPHERE OF FRENCH BEAN (PHASEOLUS VULGARIS L.) GROWING AREAS OF MANIPUR - Y. RAJLAKSHMI DEVI,; BIRESWAR SINHA, (The Bioscan, 2014)
Trichoderma spp. were collected from the rhizosphere soil of french bean from different locations of Manipur and altogether three species of Trichoderma viz. Trichoderma viride (5 isolates), Trichodera harzianum (4 isolates) and Trichoderma hamatum (1no) were isolated. The growth patterns of antagonists were observed highest on Potato dextrose agar followed by two other growth media. Colours of the Trichoderma colony were showed white green to green and sometimes yellowish green to dark green. The growth of T. viride was light greenish with fluffy growth and concentric ring with dense growth at the margin of the colony except one isolate produced coconut like aroma in all the three media, growth of T. harzianum was fast to very fast with whitish greenish to green color, concentric ring, and hyaline hyphae without any significant aroma and in T. hamatum, it was fast with whitish green to greenish colour, highly fluffy and compact colony, hyaline hyphae without any significant aroma in all the three media. Anamorphic characters viz., size of phialides, phialospore and conidiophores of all Trichoderma spp were ranges from 3.7–8.4X1.2-3.7μm, 1.6-5.2X1.2-2.7μm and 4.2-38.8-2.1-5.8μm.